Using a Monte-Carlo model to identify best filler arrangement in thermally conductive materials. Issue 12 (December 2015) - Descamps, P.; Van Wassenhove, G.; Teixeira, S.; Beaucarne, G.
Abstract: A 2D Monte-Carlo model was built to calculate the probability of paths creation between the two interfaces of a TC material via direct contact between filler particles. This model allowed studying the impact of the filler size with respect to the distance between the two interfaces on the probability of direct TC paths creation. Calculation is carried-out considering one single filler size and a mixture of two fillers of different dimensions. The material was divided in a grid and the filler loading was expressed as the % of cell occupation by a particle. We demonstrated that for any degree of filler loading, it is beneficial to use large size particles compared to the distance between the two interfaces. The calculated equivalent thermal conductivity shows a maximum impact of filler particles size for 50% of cell occupation.